Evaluasi Anggaran Biaya Produksi Pada PT. Perkebunan Nusantara III Di Kota Medan - Sinta Kismi Hana; Beby Mashito Batu Bara; Nina Angelia (Universitas Medan Area, 2019)
The purpose of this research is to evaluate the production cost budget at PT. Perkebunan Nusantara III This research is a study that uses a qualitative approach with a descriptive method in question is to use information data obtained at the time of the study and from the field in the form of data that is written or oral from the parties involved. The results obtained that PT. Perkebunan Nusantara III has evaluated the calculation of production costs periodically, based on reports based on production prices, selling prices and profit and loss by determining harvest costs, maintenance costs, factory overhead costs, processing costs, and depreciation costs. budget prepared by PT. Perkebunan Nusantara III is not yet perfect enough because there are still many significant deviations both beneficial and adverse. This is the responsibility of managers to conduct more in-depth evaluations to make the realization of costs so as not to occur too far away. Conclusions through field research that PT. Perkebunan Nusantara III has made a production cost budget with a yearly period. PT. Perkebunan Nusantara III has evaluated the calculation of production costs periodically, based on reports based on production prices, selling prices and profit and loss by determining harvest costs, maintenance costs, factory overhead costs, processing costs, and depreciation costs. The budget prepared by PT. Perkebunan Nusantara III is not yet perfect enough.